Neolithic ceramic complex of the settlement of Mergen 6 in the Lower Ishim (groups I and II): characteristics and interpretation - Enshin D.N. (Вестник археологии, антропологии и этнографии, 2021)
The article discusses a ceramic complex (groups I and II) of the early Neolithic settlement of Mergen 6 (Lower Ishim River region, Western Siberia, 7th millennium BC). The aim of the work is to analyze the materials from the perspective of the cultural and chronological correlation of the Boborykino and Koshkino antiquities of the Trans-Urals. The research is based on the elements of the historical-cultural and formal-classification approaches. The source base consists of 236 vessels. As a result of the analysis carried out in several stages (morphology of the vessels, tool and technique for applying ornamentation, structural components of the decor, nature of the system organization of the ornamental components, relationship of the image components with the structure of the vessels' shape), it was found that the products of group I correspond to the Boborykino cultural tradition, and group II — to the Koshkino. The simultaneous occurrence of these vessels made it possible to speak of the coexistence within the same society of representatives of the traditions of their manufacture. On this basis, there has been proposed a clarification of several positions regarding the pattern of the cultural and chronological development of the Boborykino antiquities in the Trans-Urals. The emergence of an early flat-bottomed ceramic complex in the River Ishim region allows it to be included in the range of materials of a similar appearance (Satyginsky, Mulymyinsky, Amninsky, Kayukovsky, Barabinsky) identified in the mountain-forest Trans-Urals, Kondinsky lowlands, Irtysh River region and Baraba. Identification of the Mergen vessels of group I as belonging to the Boborykino Culture, dating from the Early Neolithic, makes it possible to pose the question of identifying the early phase of the antiquities of this cultural group. Location of the Koshkino and Boborykino groups of vessels in the same sites attests to the coexistence and contacts of the two traditions and their mutual influence.